Challenges of Zakat Integration as Source of State Revenue - Yasni, Raynal; Erlanda, Agam Reynaldi Reza (International Journal of Islamic Economics and Finance (IJIEF), 2020)
In the era of new public financial management, where society participation and cost sharing in public goods provision are inevitably pursued by government, some sources can still be explored such as zakat, infaq, and sadaqah as social awareness activities for Muslims that are prevalent in the community. There are also other donations on the basis of certain motivations which can reduce the burden of tax revenue to support public policy. The phenomenon of mutual cooperation and caring to help others through social donations emerged even more apparent when the Covid-19 pandemic entered a period of social restrictions. This study aims to examine the challenges faced in integrating zakat as an alternate state revenue. The method used is descriptive qualitative using primary data in the form of semi-structured interviews. Determination of the source of data on the interviewee is done purposively. They are chosen to represent zakat practitioners, representatives of government and taxation institutions, and academics. The results showed various challenges in integrating zakat as an alternative source of state revenue, namely uniting government programs with receivers, distribution process, strong zakat institutions, supervisory institutions, public trust, increased compliance, issues on state ideology, alignment of rules with other religious communities, revenue earmarking, and spending flexibility.